The The Interpersonal Meaning in Trump’s Victory Speech - Savitri, Andini Syita; Warsono, Warsono (English Education Journal, 2019)
This study deals with analyzing language used for communication. It analyzes a victory speech by Donald Trump as the newest president of America from the perspective of SFL especially dealing with the Tenor of the discourse of the speech. In other words, this study is about interpersonal meaning of the speech which can be used to dig up speaker’s attitudes towards what s/he is saying in the speech. In conducting this study, I had two objectives to achieve. First, this study tried to understand the interpersonal meaning of Donald Trump’s victory speech by looking deeply on the Mood system of the clauses of the speech which means analyzing the two constituents of Mood which are Subjects and Finites of the clauses in the speech. Second, it also tried to uncover Donald Trump’s attitudes towards Americans by applying the Appraisal theory proposed by Martin. Appraisal offers an ideal analytical framework to systematically identify interpersonal meanings in language. The result of analysis showed that the most subject found in the speech was I – Donald Trump which meant that Trump himself was responsible to what he was saying in the speech. The Finites in the speech were mostly stated in Simple Present Tense which was meant that in delivering his speech, Trump gave the general truth at the moment of the speaking. Since most of the clauses were declarative clauses, Trump was considered to share information in this case he share his vision and mission for future America to the audience. That shared information was further analyzed with the Appraisal theory which led to the conclusion that Trump gave positive attitudes towards Americans. Based on this study, finally we come to an understanding that it’s important to understand any kinds of speech well. One among ways to do it is by analyzing that speech through its interpersonal meaning and its appraisal system. This study is useful for readers, especially English Department students in order to be able to understand the meaning behind a text well.